1998
DOI: 10.1046/j.1365-2346.1998.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic suggestions given during neurolept-anaesthesia decrease post-operative nausea and vomiting

Abstract: A double-blind randomized study was performed in 100 patients undergoing thyroidectomy to evaluate the effect of positive therapeutic suggestions made during neurolept-anaesthesia. The classic droperidol-fentanyl-N2O technique was used as these drugs preserve the neurophysiological functions required to process the information in the therapeutic suggestions given during general anaesthesia. Patients in the suggestion group heard positive non-affirmative suggestions during the whole operation. An autoreverse ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Two reported short-lasting PONV relief directly after surgery but not later that day, 62 , 63 while three studies found PONV to be reduced when patients had been exposed to positive therapeutic suggestions. 60 , 64 , 65 Postoperative antiemetic requirement was assessed in seven studies, but given the different auditory interventions and data presentation, no meta-analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two reported short-lasting PONV relief directly after surgery but not later that day, 62 , 63 while three studies found PONV to be reduced when patients had been exposed to positive therapeutic suggestions. 60 , 64 , 65 Postoperative antiemetic requirement was assessed in seven studies, but given the different auditory interventions and data presentation, no meta-analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative opioid requirements were assessed in 12 studies, with nine included in the metaanalysis. [52][53][54][55][56][57][59][60][61] Intraoperative music significantly reduced postoperative opioid requirements (pooled SMD, -0.29; 95% CI, -0.57 to -0.02; P = 0.04; I 2 = 36; n = 336 patients in five studies), whereas positive therapeutic suggestions did not (pooled SMD, -0.12; 95% CI, -0.40 to 0.16; P = 0.41; I 2 = 39; n = 372 patients in five studies) (Fig. 3).…”
Section: Explicit Memory Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been a handful of studies that have looked at the efficacy of using audiotapes to provide the hypnotic intervention (Johnson and Wiese, 1979; Hart, 1980; Block, Ghoneim, Sum Ping and Ali, 1991; Enqvist, Bjorklund, Engman and Jakobsson, 1997; Eberhart, Doring, Holzrichter, Roscher and Seeling, 1998; Perugini, Kirsch, Allen, et al, 1998; Forbes, MacAuley, Chiotakakou-Faliakou, 2000; Ghoneim, Block, Sarasin, Davis and Marchman, 2000). These studies have yielded mixed results.…”
mentioning
confidence: 99%